Safety and efficacy of l‐tryptophan produced by fermentation with Escherichia coli KCCM 80135 for all animal species. (7th May 2019) - ; Bampidis, Vasileios; de Lourdes Bastos, Maria; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; Pechová, Alena; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on l ‐tryptophan produced by fermentation using Escherichia coli KCCM 80135 when used as a nutritional additive in feed and water for drinking for all animal species. The production strain and its recombinant DNA were not detected in the additive. l ‐Tryptophan produced by fermentation with E. coli KCCM 80135 does not raise any safety concern with regard to the genetic modification of the production strain. The use of l ‐tryptophan produced using E. coli KCCM 80135 in supplementing feed to compensate for tryptophan deficiency in feedingstuffs is safe for non‐ruminant target species. Using unprotected forms of tryptophan in ruminants can be a risk. The use of l ‐tryptophan produced by fermentation using E. coli KCCM 80135 in animal nutrition presents no safety concerns to consumers of animal products. l ‐Tryptophan produced by E. coli KCCM 80135 is not toxic by inhalation. The additive is not an irritant to skin and eyes, and it is not a skin sensitiser. The additive under assessment is considered safe for the environment. It is regarded as an effective source of the amino acid l ‐tryptophan for all non‐ruminant species. If the additive l ‐tryptophan is intended for use in ruminants, it should be protected from ruminal degradation.